Black butler. 21 - Toboso, Yana, 1984- (Yen Press, 2015)
"With the helpful hand of his distinguished butler, Sebastian, Earl Ciel Phantomhive, once again with his wits about him, discovers the reality of both the Emerald Witch and the curse of the Wolfman that haunts a small village in the forests of Germany. On the orders of Her Majesty, Queen Victoria, master and servant escort the young sheltered Emerald Witch, Lady Sullivan, beyond the doors of the Emerald Castle and into the outside world...only to find themselves right in the path of an oncoming German special forces attack?!" --